Structural feature of Cu64Zr36 metallic glass on nanoscale: Densely-packed clusters with loosely-packed surroundings. (1st April 2016) - Feng, S.D.; Qi, L.; Wang, L.M.; Yu, P.F.; Zhang, S.L.; Ma, M.Z.; Zhang, X.Y.; Jing, Q.; Ngai, K.L.; Greer, A.L.; Li, G.; Liu, R.P.
Abstract: The structure of Cu64 Zr36 metallic glasses is investigated on the scale of nanometers using local shear strain marking in molecular dynamics simulation. Densely packed clusters with sizes ranging from 1.5 to 2.5 nm are unambiguously shown comparable to the size of the reported medium range order, surrounded by loosely packed interconnecting regions with a low density. The clusters are mainly composed of full and defective icosahedra, while no dominant short-ordered motifs are identified in the surroundings. High resolution transmission electron microscopy reproduces the observation of simulations. Graphical abstract: